2016
DOI: 10.1016/j.vetpar.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, biological, and morphometric comparisons between different geographical populations of Rhipicephalus sanguineus sensu lato (Acari: Ixodidae)

Abstract: In this study, different geographical populations of Rhipicephalus sanguineus sensu lato were compared by molecular, biological, and morphometric methods. Phylogenetic trees were constructed using 12S and 16S rDNA sequences and showed two distinct clades: one composed of ticks from Brazil (Jaboticabal, SP), Cuba (Havana) Thailand (Bangkok) and the so-called "tropical strain" ticks. The second clade was composed of ticks from Spain (Zaragoza), Argentina (Rafaela, Santa Fe) and the so-called "temperate strain" t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 27 publications
4
25
1
3
Order By: Relevance
“…in the Neotropical region: tropical species (occurring from northern Mexico, Central America, and tropical areas of South America) and temperate species (found temperate and cold localities from the southern cone of South America) [57]. This notion is supported by more recent studies [810], indicating that ticks currently identified as “ R. sanguineus ” actually belong to at least two distinct species.…”
Section: Discussionmentioning
confidence: 85%
“…in the Neotropical region: tropical species (occurring from northern Mexico, Central America, and tropical areas of South America) and temperate species (found temperate and cold localities from the southern cone of South America) [57]. This notion is supported by more recent studies [810], indicating that ticks currently identified as “ R. sanguineus ” actually belong to at least two distinct species.…”
Section: Discussionmentioning
confidence: 85%
“…[92], Sanches et al . [93] who divided the R. sanguineus group into tropical and temperate strains. On the other hand, the phylogenetic tree of 18S rDNA gene sequence (KU198407), placed the Egyptian brown dog tick in a separate clad that may return to 18S rRNA identified at genera level (KF958435.1) [51], subsequently, doubted the usefulness and applicability of such gene in molecular taxonomy of ticks (Figure-7a).…”
Section: Discussionmentioning
confidence: 99%
“…The specific taxonomic classification of R. sanguineus sensu lato remains subject to ongoing debate (Dantas‐Torres, ; Moraes‐Filho et al ., ; Nava et al ., , ; Dantas‐Torres et al ., ; Dantas‐Torres & Otranto, ; Sanches et al ., ). According to Nava et al .…”
Section: Introductionmentioning
confidence: 97%
“…Other authors have supported and extended these findings by suggesting the existence of at least two climate‐related lineages based on climate variables correlation analysis and including a ‘tropical lineage’ and a ‘temperate lineage’ (Szabó et al ., ; Moraes‐Filho et al ., ; Sanches et al ., ; Zemtsova et al ., ). Recently, (Dantas‐Torres et al ., ) highlighted four genetically distinct morphotypes in R. sanguineus s.l ., designated as Type I (from Greece), Type II (from Italy, France, Spain and Portugal), Type III (from India) and R. sanguineus s.l .…”
Section: Introductionmentioning
confidence: 99%